Outsourcing of IT and Absorptive Capacity: A Multiple Case Study in the Brazilian Insurance Sector - Valter Moreno; Marcello A. S. Coelho; Claudio Pitassi (BBR: Brazilian Business Review)
Sources of external knowledge are critical to the implementation of strategies to achieve innovation, especially in the case of information technology. The concept of absorptive capacity reflects the ability of firms to obtain, assimilate, combine, and extract advantages from external knowledge to generate innovations. The objective of this multiple case study was to investigate how outsourcing of IT can influence the absorptive and innovative capacity of organizations, focused on the insurance sector. The results of comparing four insurers with different degrees of innovation and adoption of IT outsourcing indicate that the connections between the strategy of relationship with suppliers and the stance of the IT area of the client company, and its previous activity and level of knowledge, are essential to determine the absorptive and innovative capacity. Besides this, companies that neglect outsourcing of IT to leverage their absorptive and innovative capacity can suffer significant harm regarding the use of resources, agility, and competitiveness.